DCH Logistics - planning for La Cafetie`re - Yeung, Jeff; Zhao, Xiande; Lam, Kokin (London : NeilsonJournals Publishing, 2011)
The study demonstrates the approach of global supply chain restructuring by DCH Logistics, a world-renowned Hong Kong-based third-party logistics service provider (3PL) for its client La Cafetie`re in the area of warehousing and transportation as well as customer services such as packaging, procurement, custom declaration, bonded warehousing, hygiene and quarantine. The case enables insights into the advantages of having a local logistics services provider that knows the local market, environment and regulations specifically to shorten the supply chain leadtime, reduce inventory level, and most importantly improve customer satisfaction as well as other comprehensive supply chain activities. Furthermore, the case develops common supply-chain issues multi-nationals face on an operational level, especially in China.
Originally Published InYeung, J., Zhao, X., & Lam, K. (2011). DCH Logistics -- Planning for La Cafetie`re. Operations Management Education Review, 5(1), 109-134. OMER5-0CS1.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; DCH Logistics -- Case studies; La Cafetie`re -- Case studies; Business planning -- Case studies; Business logistics -- Case studies